2015
DOI: 10.1016/j.toxrep.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective potential of antioxidant potent fraction from Urtica dioica Linn. (whole plant) in CCl 4 challenged rats

Abstract: The aim of the present study was to isolate hepatoprotective component from Urtica dioica Linn. (whole plant) against CCl4-induced hepatotoxicity in-vitro (HepG2 cells) and in-vivo (rats) model. Antioxidant activity of hydro alcoholic extract and its fractions petroleum ether fraction (PEF), ethyl acetate fraction (EAF), n-butanol fraction (NBF) and aqueous fraction (AF) were determined by DPPH and NO radicals scavenging assay. Fractions were subjected to in-vitro HepG2 cell line study. Further, the most poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 52 publications
2
29
0
1
Order By: Relevance
“…[28,33] Normal hepatocytes are used as in vitro model for studying the in vitro xenobiotics metabolism and toxicity to the liver. [4] In this study, HepG2 cells were used that minimized any species related differences and maintained majority of specialized function like cell viability, which directly referred the extracellular stress response. Among all the extracts, EAE significantly inhibited the ROS in a dose-dependent manner (IC 50 80.93 ± 1.02 µg/mL), which was comparable to silymarin (IC 50 76.11 ± 0.96 µg/mL) and resulted in increased cell viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28,33] Normal hepatocytes are used as in vitro model for studying the in vitro xenobiotics metabolism and toxicity to the liver. [4] In this study, HepG2 cells were used that minimized any species related differences and maintained majority of specialized function like cell viability, which directly referred the extracellular stress response. Among all the extracts, EAE significantly inhibited the ROS in a dose-dependent manner (IC 50 80.93 ± 1.02 µg/mL), which was comparable to silymarin (IC 50 76.11 ± 0.96 µg/mL) and resulted in increased cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 20000 deaths and 250000 new cases have been reported every year worldwide. [3,4] The available synthetic drugs such as interferon and corticosteroids for treatment of hepatic disease are expensive and may cause further damage.…”
Section: Introductionmentioning
confidence: 99%
“…The present study suggest that, the phenolic compound of U. dioica has a protective role against CCL4 that may lead to decrease regucalcin level in serum via decreasing attracting of CCl4 with liver membrane and to increase membrane fluidity, as well as, damage to membrane protein and to increase of membrane antioxidant defence enzyme because of this richness of U.dioica with phenolic compound that may provide a good source of antioxidant these findings are in accordance the other findings. 50,51 Study of the effect of AgNPs on Regucalcin level: Table-2, Figure-3 and Figure-4 showed a significant decrease in regucalcin level after oral administration of silver nanoparticles. Kataki et al and Sung et al mentioned that liver was the main target organ for AgNPs and the hepatoprotective effect of nanoparticles depend on the size of particles, therefore, the toxicity of smaller particles produce the more cytotoxic response.…”
Section: Study Of the Effect Of Udioica On Regucalcin Levelmentioning
confidence: 99%
“…The leaves extract of plant shows maximum hepatoprotective activity at dose of 400 mg/kg concluded by the decreased level of serum alanine transaminase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total bilirubin level and malonyldehyde (MDA) and also by the increase in level of superoxide dismutase (SOD) level 67,68 . The seed extract of Urtica dioica has also shown hepoatoprotective protective activity against ischemia-reperfusion induced hepatotoxicity and it exhibited hepatoprotective effect by increasing the activity of paraoxonase, aryl-esterase and liver tissue catalase activity 69 .The plant extract has shown significant hepatoprotective effect in isolated rat hepatocytes (in vitro) and in rabbits (in vivo) reduces the chances of hepatocellular degeneration and necrotic changes in CCl 4 induced hepatotoxicity 70,71,72 .…”
Section: Antioxidantmentioning
confidence: 99%